Guide to International Relations and Diplomacy. - Fry, Michael Graham (Bloomsbury Publishing, 2002)
This encyclopedic-style guide to international relations and diplomacy consists of 900 entries, arranged broadly by key concepts, such as diplomatic relations; diplomatic agreements; force and diplomacy; doctrines; policies and tactics, etc. moving from the general and structural issues of the global system to more detailed events, crises and war. The editors draw together a large quantity of background and contextual information on the evolution and functioning of the global international system in one volume. It covers the time period from the Vienna Congress in 1815 to the present.